Evaluation of reliability of L escriptiqn of termutagiphie patterns - Zamorski, Andrzej (Anthropological Review, 1984)
This work attempts to determine the error risk existing in the qualitative determination of dermatoglyphic patterns made within a definite classification system. This problem was examined in reference to the Lestrange-Bochenska classification (Bocheńska, 1964) frequently used in Poland. The material consisted of finger-prints taken in 1981 from students, Each print was described independently by four examiners. The calculational analysis of the obtained results was made by two methods: a variation method, and a method examining the degree of description repeatability: In both methods two evaluation criteria were taken into account: criterion I — total agreement of the figure description was examined, ie, the type and orientation criterion II — moderated, reflecting the degree of description convergence only in reference to the pattern type. The obtained results permit a statement that a 100% agreement of description has not been obtained for any of the studied aspects. The identity level of finger- -prints description ranges from 0.979 (for the loops) to 0.355 (for the bicentric whorl W?). This indicates the need of a modification in the classification system for finger patterns.